PERAN INOVASI DAN KEUNGGULAN BERSAING DALAM MEMEDIASI DAMPAK ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN PADA INDUSTRI KECIL DAN MENENGAH YANG BERBASIS PANGAN LOKAL DI KOTA TERNATE - Abdullah Wajir Jabid; Sulfi Abdul Haji; Rahmat Sabuhari; Marwan Man Soleman (Universitas Bina Taruna Gorontalo, 2024)
This research aims to analyze the impact of entrepreneurial orientation on marketing performance, both directly and through innovation and competitive advantage variables as mediators. The sample used was 83 respondents who were small and medium industrial entrepreneurs based in the food industry in Ternate City. The sampling technique used is probability sampling, where this sampling technique provides opportunities for local food industry practitioners as elements of the population to be selected as respondents. The analytical method for testing hypotheses is SEM-PLS. The research results show that entrepreneurial orientation has a positive and significant effect on innovation, competitive advantage and marketing performance. then the innovation and competitive advantage variables have a positive and significant effect on marketing performance. Further research findings can also show that innovation and competitive advantage variables play a role in mediating the influence of entrepreneurial orientation on marketing performance.